Drum Set Training in Music Therapy: A Resource for Students, Clinicians, and Educators. Issue 1 (16th June 2020) - Matney, Bill
Abstract: The field of music therapy commonly uses percussion instruments. To some degree, the drum set has been included in the literature. Percussion training, and in this case drum set training, specific to music therapy practice have likely lagged behind the instruments' uses in the field, potentially resulting in limitations to effective practice. Andragogically speaking, the field benefits from resources that take into account the needs of students and clinicians, while also addressing training program challenges (such as time and accessibility of drum sets). The purpose of this article is to provide an approach to learning the drum set that promotes relevant use and relevant play, without necessarily always needing to be at a drum set to practice. The author first situates the history of the drum set and discusses its common set up and use. Through the use of body percussion, vocalizing/singing, and other processes, the author proposes a way to promote a stronger understanding of how to use the drum set for accompaniment, recreating, composing, and improvising. The author breaks down and scaffolds technical drum set tasks, but then promotes their integration. Visuals and video resources are included. The author concludes with implications for practice, training, and research.